Jelai Starch–Na-Alginate Film Reinforced with Bacterial Cellulose and Glycerol Plasticizer for Minimally Processed Pineapple Coating - Sukmiyati Agustin; Muhammad Fajar Rahmadani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Jelai is a natural source of starch that is widely found in East Kalimantan but has not been extensively explored for its utilization. Edible films from jelai starch–Na-alginate generally exhibit high hydrophilicity and poor mechanical properties. This research aimed to improve these characteristics by incorporating bacterial cellulose (BC) as a filler and glycerol as a plasticizer, and to evaluate the effectiveness of the optimal formulation on minimally processed pineapple. The study utilized a Factorial Completely Randomized Design with two factors: BC concentration (0.1%, 0.2%, 0.3%) and glycerol concentration (0.5%, 1.0%, 1.5%) with 3 replications. The data were analyzed using ANOVA, and continued with Tukey’s test. The results showed that the interaction between BC and glycerol significantly affected solubility and tensile strength. Glycerol significantly affected thickness, Water Vapor Permeability (WVP), and elongation. The best treatment (0.3% BC and 1.0% glycerol) yielded a tensile strength of 14.0 MPa, elongation of 4.39%, solubility of 44.23%, and WVP of 0.03716 g⸳mm⸳kPa–1⸳day–1⸳m–2. The optimized coating effectively maintained a significantly higher pH (p < 0.05) in minimally processed pineapple than the control during 8 days of storage, indicating its potential to slow acidification and preserve product stability. The addition of BC and glycerol successfully improved the mechanical properties of the film and showed potential for maintaining pH stability in fresh-cut fruits.